Case Report: A novel hemizygous missense PDHA1 variant in a Vietnamese boy with pyruvate dehydrogenase E1-alpha deficiency - Nguyen, Thi Thanh Ngan; Khanh, Nguyen Ngoc; Vu, Chi Dung; Nguyen, Ngoc-Lan; Tran, Van Khanh; Lien, Nguyen Thi Kim; Van Tung, Nguyen; Quan, Nguyen Duc; Hien, Nguyen Thanh; Giang, Tran Thi Huong; Xuan, Nguyen Thi; Tao, Nguyen Thien; et al. (Frontiers in Pediatrics, 2024)
The pyruvate dehydrogenase complex deficiency causes adenosine triphosphate (ATP) down-production and energy insufficiency, leading to neurological disorders. Abnormal E1-alpha protein originating from the PDHA1 gene with pathogenic variants is unable to communicate with the E1-beta for the formation of E1 enzyme, decreasing pyruvate dehydrogenase complex activity. In this study, we report a Vietnamese boy with lethargy, severe metabolic acidosis, increased serum lactate, hyperalaninemia, lactic acidosis, and globus pallidus lesions. Whole exome sequencing and variant filtering identified a hemizygous missense variant NM000284.4 (PDHA1): c.479T>G (p.Phe160Cys) in the patient. The variant c.479T>G caused a single nucleotide substitution on the exon 5 and was predicted as a disease-causing variant by in silico analyses. We present the first report on genetic analysis of Vietnamese patient with pyruvate dehydrogenase E1-alpha deficiency. Sanger sequencing demonstrated that the patient inherited the variant from his mother. Even though the patient’s mother harbored the variant at the heterozygous state, no PDHAD symptoms were observed. Additionally, a prenatal test of the patient’s mother revealed the fetus of a normal genotype. However, the patient’s father and sister both carried a normal allele. Based on the American College of Medical Genetics criteria, the variant c.479T>G was interpreted as a likely pathogenic variant. In combination the genotype and phenotype, the patient was definitely diagnosed with pyruvate dehydrogenase E1-alpha deficiency. Our findings can expand mutational spectrum of the neurological disorders and provide the scientific basis for genetic counseling for the patient’s family.